Study Characterization of White Light Generation from Light Emitting Device (Eurasian Journal of Research, Development and Innovation, 2024)
From the previous work one can summarized the conclusions as follows: Fabrication of EL-device from semiconductors material (ZnS QDs) with hole injection organic polymer (TPD) was effective in white light generation and can be the color of emerged light. After adding the Alq3 layer of the hybrid device form ITO/TPD:PMMA/ZnS QDs/Alq3/Al was obtained as follows: 1. The alignment of OLED between two organic molecules leads to the generation of high energy improves the properties of the hybrid device. 2. The output current from I-V characteristics is good compared that with Alq3 few voltages (at 6V). 3. Recombination processes would give rise to the forward bias current flow is faster. 4. The intensity emission of EL hybrid device is very high. White light generated is very clear and high efficiency